ENGLISH LANGUAGE ERROR ANALYSIS OF DESCRIPTIVE TEXT PRODUCED BY SEVENTH GRADER - Laili, Muawwinatul (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
This study aims to describe the error on descriptive text written by seventh C grader in SMPN 1 Porong and to identify the causes of error. The research method of this research is descriptive qualitative method. The researcher used interactive model by Miles and Huberman that consists of three steps, they are; data condensation, data display, and drawing verifying conclusions. The researcher used the document observation sheet and questionnaire form as the instrument of this research. The researcher only selected 20 descriptive texts written by the students. Based on the research finding, it can be concluded that the students produced error on their descriptive texts. The highest error is miss-formation error (48,87%) because the students lack on writing practice. The researcher found the causes of error from the questionnaire is communication strategy-based error as 50% because the students get misunderstanding in receiving descriptive text material from the teacher's explanation. The teacher should change the method in the teaching process to help the students understand descriptive text well. For the next researcher, this research can be a reference for error analysis on other English skills.